HIGH-FAT DIET IN THE PERI-PUBERTAL PERIOD PROGRAMS CARDIOVASCULAR DYSFUNCTION IN ADULT MALE WISTAR RATS - Maiara Vanusa Guedes Ribeiro; Anna Rebeka F. Oliveira; Maria Natália C. Peres; Silvano Piovan; Lucas A. Ferreira; Rodrigo M. Gomes; Paulo Cezar F. Mathias; Kesia Gemima Palma Rigo Wutzow (Arquivos do Mudi, 2023)
Stress during peri-pubertal period can determine no communicable disease in adulthood. Thisstudy aims to evaluate whether high fat diet exposure during adolescence induces long-termcardiovascular dysfunctions. The ethic committee approved the animal protocol nº1527130815. Wistar rats, 30-days-old, were feed to a high fat diet (HFD, 35% lard w/w) until60-days-old, then fed a normal fat diet for a further 60 days dietary recovery. Control animalsate normal fat diet throughout life. Body weight and food intake were evaluated weekly. AtPN120, cardiovascular and histological analysis were done. Student´s T test were applied.PN120, feed by HFD during adolescence increase systolic and diastolic blood pressure (upper10% and 4%, respectively; p <0.05 and p <0.005). Using ganglionic blocker, hexamethonium(30 mg/kg, iv), blood pressure was greater in the HFD rats (26%; p <0,01). Increasedperivascular and interstitial fibrosis (42% and 62% respectively; p<0,01 and p<0,001) wereobserved in the HFD rats, accompanied by a left ventricular hypertrophy (29%; p<0,001).Rats who were fed with HFD during peri-pubertal age present hypertension, hyperactivity ofthe vascular sympathetic nervous system and morphological cardiac alterations in adulthood.Current study remarks that adolescence is a plastic phase which permit to programs diseaseslater in life.